Evaluation of Bone Mineral Metabolism in Pre-Dialysis Chronic Kidney Disease: Quantitative Computed Tomography vs. Dual-Energy Absorptiometry and Correlation with Bone Turnover Markers - Aydan Mutis Alan; Zehra Sezer; Ahmet Oz; Cebrail Karaca; Mevlüt Tamer Dinçer; Ahmet Murt; Fatma Beyza Sag; Selma Alagoz; Serdar Sahin; Mustafa Sait Gonen; Elif Güzel; Sinan Trabulus; et al. (Medicina)
Background and Objectives: Bone and mineral disease (BMD) is a prevalent complication of advanced chronic kidney disease (CKD). The risk of fractures can be assessed via dual-energy X-ray absorptiometry (DXA) and quantitative computed tomography (QCT). This study aims to evaluate the effectiveness of two imaging modalities in identifying bone mineral status in individuals with pre-dialysis chronic renal disease and to assess their correlation with bone turnover markers. Materials and Methods: This controlled cross-sectional study, conducted at a single center from 2019 to 2022, assessed two groups of individuals aged 18 to 50. The patient cohort consisted of individuals with stage 4–5 chronic kidney disease, whereas the control cohort consisted of healthy participants. The participants’ bone and mineral status was evaluated using both QCT and DXA methods. Diagnostic measurements of the lumbar spine and femoral neck, obtained using DXA and QCT, were compared. Z-scores were utilized to evaluate low bone mineral density, with low Z-scores identified in either lumbar spine or femoral neck measures being seen as indicative of low bone mineral density. Results: Data from 38 participants (patient group: 18; control group: 20) who underwent QCT and/or DXA were evaluated. Thirty-three subjects were assessed using both QCT and DXA (patient group: 14; control group: 19). The median age of the patient cohort was 44 (range: 22–50), whereas the median age of the control cohort was 42 (range: 27–48) (p = 0.72). Women constituted 33% of the patient cohort and 50% of the control cohort (p = 0.23). In the patient cohort, low bone mineral density was detected in four individuals (28%) through QCT, and in just two patients (14%) through DXA. Compared to DXA, QCT identified a higher number of cases of low bone mineral density in the CKD cohort; however, no statistically significant difference was observed (p = 0.06). In addition, our study found that TRACP5b had a strong negative correlation with the DXA L1–L4 Z-score. Conclusions: This study revealed that QCT may be more sensitive than DXA for detecting low bone density in pre-dialysis CKD patients. Additionally, DXA may overestimate lumbar spine BMD in this population, and the strong negative correlation between TRACP5b levels and the DXA L1–L4 Z-score highlights the potential role of biochemical markers in assessing bone status in CKD